Joseph Cowles Mehaffey papers - Mehaffey, Joseph Cowles, 1889-1963.
Correspondence, reports, notes, articles, pamphlets, clippings, and other papers relating primarily to life in the Canal Zone and to the operation of the Panama Canal. Other subjects include the Panama Railroad Co., Central America, Panama, and Mehaffey's various engineering projects, including Arlington Memorial Bridge (Va.) and renovation of the White House.
Library of Congress Prints and Photographs Division.
U.S. Army engineer and governor of the Panama Canal Zone.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Panama Railroad Co; White House (Washington, D.C.); Bridges -- Potomac River; Canals -- Panama; Civil engineering; Public buildings -- Washington (D.C.); Railroads -- Panama; Arlington Memorial Bridge (Va.); Canal Zone -- History; Canal Zone -- Social life and customs; Central America -- History; Panama -- History; Panama Canal (Panama); Engineers; Governors -- Canal Zone